2004
DOI: 10.1097/01.cpm.0000117766.07651.f8
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Lung Disease

Abstract: Chemotherapy-induced lung disease (CILD) can be caused by multiple agents. The diagnosis should be considered in any patient who develops pulmonary symptoms during or after treatment with chemotherapy. It is a diagnosis made by exclusion of other etiologies, especially recurrent tumor or infection. The most common clinical presentations are interstitial pneumonitis/fibrosis, hypersensitivity pneumonitis, and capillary leak syndrome. The clinical characteristics of bleomycin, mitomycin, carmustine, and methotre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…Based on our observations, the rate of ICU admission was similar, however, Ca + patients required more mechanical ventilation. This may be due to the adverse effects of prior chemotherapy or radiotherapy on the respiratory capacity of patients (16,17). In a retrospective analysis, Miyashita et al (3) found that a history of cancer significantly increased the intubation rate in patients aged 66 -80 years [relative risk (RR):1.76, 95% CI 1.15 -2.70].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our observations, the rate of ICU admission was similar, however, Ca + patients required more mechanical ventilation. This may be due to the adverse effects of prior chemotherapy or radiotherapy on the respiratory capacity of patients (16,17). In a retrospective analysis, Miyashita et al (3) found that a history of cancer significantly increased the intubation rate in patients aged 66 -80 years [relative risk (RR):1.76, 95% CI 1.15 -2.70].…”
Section: Discussionmentioning
confidence: 99%
“…Presentation is characterized by dyspnoea, non‐productive cough and often fever 2 . No radiographic or pathologic finding is pathognomonic for chemotherapy‐induced lung disease and therefore the diagnosis is based on the temporal relationship, type of clinical presentation and the exclusion of infection or progression of the neoplastic process by invasive procedures 35 . Flow cytometry of BAL specimen has been reported to differentiate CPA toxicity from lymphoma progression 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Самый серьез ный побочный эффект блеомицина заключается в его токсичности относительно легких. С примене нием блеомицина связано несколько отчетливых ле гочных синдромов, таких как облитерирующий бронхиолит с организующей пневмонией [9], эози нофильная гиперчувствительность [10] и, чаще всего, интерстициальный блеомициновый пульмонит (БП), способный завершиться фиброзом легких [11]. Ле карственный пульмонит встречается с частотой до 46 % случаев применения блеомицина, в зависимо сти от критериев установления его диагноза [12], а смертность от БП может достигать 3 % от всех слу чаев применения блеомицина [13].…”
Section: патогенезunclassified